Positive Youth Development and Internet Use in a Sample of Spanish Adolescents - Diego Gómez-Baya; Anna Jean Grasmeijer; Esther López-Bermúdez; Margarida Gaspar de Matos; Ramón Mendoza (Frontiers Media S.A., 2022)
During the COVID-19 pandemic, the use of Internet in the adolescent population has increased. A growing research interest has been developed about the consequences of Internet use for adolescent development. Despite most studies have examined the impact of Internet use on some indicators of psychological maladjustment, few studies have addressed the detrimental impact on the positive indicators of mental health. Positive youth development (PYD) represents a positive view of adolescent transition to adulthood which focuses on building the strengths that make young people more resistant to negative outcomes and more capable to choose a positive life direction. This study aimed to analyze the relationships between different aspects of Internet use and overall PYD in a sample of Spanish adolescents. To reach this aim, a sample of 1,038 adolescents (50.1% boys, M age = 14.19, SD = 1.38), enrolled in 14 high schools in the city of Huelva (Spain), filled in some self-report measures of PYD and Internet use and experience, such as the frequency of Internet use on weekdays or weekends, the different uses of Internet (i.e., social networks, playing online, reading, surfing or looking for information, playing or downloading music, and searching, selling, or buying products), and the subjective experience using the Internet (i.e., acknowledgment of spending too much time playing or in the networks, and being in a bad mood if they do not play or use the networks). Results of a hierarchical regression analysis showed that the more hours using Internet on weekdays, the less PYD. Moreover, the experience of feeling bad when not using the networks and spending too much time with online playing was related to lower PYD. However, the use of Internet for reading or looking for information had a positive association with PYD. These results suggest some implications for practice, such as the need to promote an adaptive Internet use, by providing a safe online context that encourages the acquisition of positive social values and life skills.